Relação entre os índices de variabilidade da frequência cardíaca, força muscular periférica, funcionalidade e aspectos nutricionais de idosos hospitalizados, sarcopênicos e frágeis - Oliveira, Marcelo Olímpio de (2024)
Introduction: The prevalence of sarcopenia and frailty is common in the elderly, making them vulnerable, with functional impairment and increasing the incidence of hospitalizations. Cardiovascular consequences, such as changes in heart rate variability (HRV) are frequent, with an even more negative impact on hospitalization. Our study aims to evaluate and verify whether there is a correlation between HRV behavior and factors that condition sarcopenia and frailty in hospitalized elderly people. Objectives: To evaluate the HRV response after postural changes and its relationship with factors contributing to sarcopenia and frailty in hospitalized elderly people. Screen for the presence of sarcopenia and frailty. Methods: This is a cross-sectional, observational study, carried out at the University Hospital of the Federal University of São Carlos (HU-UFSCar). Participants were approached to present the study within the first 72 hours of hospital admission, in the ward or emergency room. Elderly people aged 60 years or over were included, with preserved cognition to understand and carry out the proposed interventions, in addition to hemodynamic and respiratory stability. Clinical data was collected, heart rate (HR) was recorded to evaluate HRV, Charlson and Barthel comorbidity indices, questionnaires such as Sarc-f, International Physical Activity Questionnaire (IPAQ) and reduced Mini Nutritional Assessment (MANr) , Appendicular Skeletal Muscle Mass Index (IMMEA), handgrip dynamometry (FPP) and gait speed test (MVT). For statistical analysis, the Shapiro-Wilk test was applied to verify data normality, the Anova One Way or Kruskal-Wallis tests to compare data between groups, the T or MannWhitney tests to compare two groups and the Pearson or Spearman correlation. For significance, a p less than or equal to 0.05 was adopted. Results: 40 hospitalized elderly people were evaluated, with a mean age of 70.28±7.06 years, 20 men and 20 women (50% each). HRV behavior in sarcopenic and frail elderly people was correlated with IMMEA (rs 0.82, p 0.04), Barthel (rs 0.83, p 0.01), TVM (rs 0.88, p 0.01 ), FPP (rs 0.67, p 0.04), IPAQ (rs 0.92, p 0.01), MANr (rs 0.79, p 0.01) and Charlson (rs -0.59, p 0.04). The participants' HRV behavior showed similar characteristics at rest, however, given the postural change, sarcopenic elderly people showed differences in HRV values (Low Frequency - LF p 0.01; High Frequency - HF p 0.01; Low Frequency/ High Frequency - LF/HF p 0.03; Alpha 1 p 0.01). Among the participants, 31 (77.5%) met criteria for sarcopenia and 29 (72.5%) for frailty, and only 6 participants (15%) did not meet criteria for sarcopenia and/or frailty. Hospitalized elderly people had worse nutritional conditions [MANr 6.00 (5.70 - 8.79)], peripheral muscle weakness [FPP 20.00 (19.18 - 25.30)], reduced functionality [MVT 0.78 m /s (0.69 - 1.06)] and low physical activity [IPAQ 140.00 min/week (122.19 - 503.40)]. Conclusion: The results of this sample identified that better HRV indices in sarcopenic and frail elderly people were associated with greater independence, peripheral muscle strength, physical activity, functional capacity and nutritional aspects, on the other hand, worse indices were associated with a greater number of comorbidities and increased risk of mortality. HRV values at rest were similar between the sarcopenia and frailty subgroups. However, after postural variation, significant differences were found in the LF, HF, LF/HF and Alpha 1 indices between the sarcopenic subgroups, regardless of severity. The frailty subgroups did not demonstrate significant differences, suggesting a worse impairment of HRV. The majority of participants in this study presented characteristics of sarcopenia and/or frailty.